2019
DOI: 10.35940/ijrte.c6592.098319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Behavioural Biases on Investment Decision Making in Bhubaneswar Region

Abstract: Behavioural Finance has gained a lot more importance in recent era. In the fast moving world where the standard finance fails to explain the irrational behavior of the investors, behavioural finance tries to identify the cause for such behavior which otherwise called as behavioural anomalies. The purpose of this research paper is to identify such anomalies and also to examine whether the behavioural biases has any influence in the investment decision making by the retail investors. This paper also put an empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Due to recency bias, investors rely more on recent information compared to the past while making decisions (Rudiawarni et al , 2020). Media response bias arises due to the stock market reaction of media leading to volatility in the financial market (Hanna et al , 2020; Khilar and Singh, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to recency bias, investors rely more on recent information compared to the past while making decisions (Rudiawarni et al , 2020). Media response bias arises due to the stock market reaction of media leading to volatility in the financial market (Hanna et al , 2020; Khilar and Singh, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Through the content analysis technique applied in this research, we highlight a wide range of individual attributes that causes various cognitive and emotional biases while making investment decisions. From the attributes point of view, demographics such as age (Lusardi, 2019), gender (Chen and Volpe, 2002), income level (Lusardi and Tufano, 2015), years of Overconfidence (Khilar and Singh, 2019;Metawa et al, 2018;Mushinada and Veluri, 2018;Baker et al, 2018), self-attribution (Mushinada and Veluri, 2018;Baker et al, 2018), disposition (Khilar and Singh, 2019;Baker et al, 2018;Ahmed and Boutheina, 2018), media response (Khilar and Singh, 2019), representativeness (Baker et al, 2018), mental accounting (Baker et al, 2018), anchoring (Baker et al, 2018), herd (Metawa et al, 2018;Baker et al, 2018), loss aversion (Baker et al, 2018), regret aversion (Baker et al, 2018) 2 Gender Overconfidence (Khilar and Singh, 2019;…”
Section: Individual Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the preceding statement, there are a number of research holes that require more investigation. First, it was discovered that investors frequently exhibit cognitive bias by Pradhana (2018), Setiawan, et al (2018), Khilar& Singh (2020, and Kumar &Nayak (2019). These findings contrast with those of studies by Ali, et al (2017), Afriani&Halmawati (2019), and Lekovi (2020), which found no evidence of a substantial impact of cognitive bias on investing choices.…”
Section: Introductionmentioning
confidence: 92%
“…Tema yang paling banyak dibahas dalam data yang di review adalah perilaku investor berupa pengaruhnya sifat ekstrovert terhadap keputusan investasi yang terdapat pada artikel penelitian Kartini & Nahda (2021), Khilar & Singh (2019), Madaan & Singh (2019), Quaicoe & Eleke-Aboagye (2021), Lakshmi et al, (2013), Rahman & Gan (2020), Shah et al, (2018. Khilar & Singh (2019) mengemukakan bahwa Investor akan menahan diri untuk berinvestasi karena kondisi pasar yang fluktuatif dan krisis ekonomi yang pernah terjadi agar terhindar dari kerugian yang besar. Behavioral finance berkaitan dengan pengaruh psikologi terhadap investor dan perilaku irasional investor saat membuat keputusan investasi.…”
Section: Aspek Psikologi Investorunclassified